Pendampingan Ibu-ibu Posyandu dalam Penguasaan Numerasi Digital Guna Meningkatkan Layanan Kesehatan Balita - Nadiyah; Indah Arifin, Nur Hatima (Insan Kreasi Media, 2023)
Assistance for posyandu cadres in mastering digital numeracy is an initiative carried out in Karangayar Village, Paiton. Assistance activities to support all activities in health service activities carried out by posyandu cadres. In the implementation of digital numeracy, Posyandu mothers are supported to identify and overcome barriers that may arise in the process of adapting to technology. Continuous evaluation is conducted to monitor progress and assess the impact of mastering digital numeracy on under-five health services. The method used is the Asset Based Community Development (ABCD) Model, by applying the Asset Based Community Development Model, assisting Posyandu mothers in mastering digital numeracy is not just an introduction to technology, but also a community empowerment journey that stimulates collaboration, innovation, and sustainable improvement of toddler health. The results of the service activities provide the ability for posyandu cadres to master digital technology in implementing health services in Karanganyar Village, Paiton Probolinggo.